Different Transcriptomic Responses to Thermal Stress in Heat-Tolerant and Heat-Sensitive Pacific Abalones Indicated by Cardiac Performance - Chen, Nan; Huang, Zekun; Lu, Chengkuan; Shen, Yawei; Luo, Xuan; Ke, Caihuan; You, Weiwei (Frontiers in Physiology, 2019)
The Pacific abalone Haliotis discus hannai is one of the most economically important mollusks in China. Even though it has been farmed in southern China for almost 20 years, summer mortality remains the most challengeable problem for Pacific abalone aquaculture recently. Here, we determined the different heat tolerance ability for five selective lines of H. discus hannai by measuring the cardiac performance and Arrhenius breakpoint temperature (ABT). The Red line (RL) and Yangxia line (YL) were determined as the most heat-sensitive and most heat-tolerant line, respectively. Heart rates for RL were significantly lower than those of the YL at the same temperature (p < 0.05). The differentially expressed genes (DEGs), which were enriched in several pathways including cardiac muscle contraction, glutathione metabolism and oxidative phosphorylation, were identified between RL and YL at control temperature (20 °C) and thermal stress temperature (28.5 °C, the ABT of the RL) by RNA-seq method. In the RL, 3370 DEGs were identified between the control and the heat-stress temperature, while only 1351 DEGs were identified in YL between these two temperature tests. Most of these DEGs were enriched in the pathways such as protein processing in endoplasmic reticulum, nucleotide binding and oligomerization domain (NOD) like receptor signaling, and ubiquitin mediated proteolysis. Notably, the most heat-tolerant line YL used an effective heat-protection strategy based on moderate transcriptional changes and regulation on the expression of key genes.